Emergence in Elderly Patient Undergoing General Anesthesia with Xenon - Maria Sanfilippo; Ahmed Abdelgawwad Wefki Abdelgawwad Shousha; Antonella Paparazzo (Case Reports in Anesthesiology)
Introduction. It is a consensus that the postoperative cognitive function is impaired in elderly patients after general anaesthesia, and such category patient takes more time to recover. Xenon is a noble gas with anesthetic properties mediated by antagonism of N-methyl-D-aspartate receptors. With a minimum alveolar concentration of 0.63, xenon is intended for maintaining hypnosis with 30% oxygen. The fast recovery after xenon anaesthesia was hypothesized to be advantageous in this scenario. Case Presentation. We report the case of 99-year-old woman who underwent sigmoid colon carcinoma resection with colorectal anastomosis. We carried out the induction phase by propofol, oxygen, fentanil, and rocuronium bromide, and then we proceeded to a rapid sequence endotracheal intubation consequently. The patient was monitored by IBP, NIBP, ECG, cardiac frequency, respiratory rate, capnometry, TOF Guard, blood gas analysis, and BIS. For maintenance we administrated oxygen, remifentanil, rocuronium bromide, and xenon gas 60–65%. Shortly after the end of surgery the patients started an autonomous respiratory activity, and a high BIS level was also recorded. Decision was made by our team to proceed into the emergence phase. The residual neuromuscular block was antagonized by sugammadex, modified Aldrete score was implicated, and we got our patient fully awake without any cognitive dysfunction or delirium. Conclusion. The rapid emergence to full orientation in very elderly patient who had been anesthetized by xenon shows concordance to the high BIS values and the clinical signs of the depth of anesthesia.